US college women's understandings of definitions of intimate partner violence. (April 2022) - Rich, Rebecca; Evans, Jennifer L.; Klimek, Sally; Wilson, Lucy
Objective: Past research suggests students have differing definitions of sexual assault, violence and intimate partner violence (IPV). To adequately develop violence prevention efforts, it is important to examine how college students understand these terms and associated behaviours. The purpose of this study was to identify which behaviours are categorised as IPV by college women and whether there are any 'grey areas' when it comes to IPV. Design: A three-phase e-Delphi study was conducted with US college women to reach consensus on the behaviours commonly associated with IPV. Setting: The study was conducted in one large, Southeastern USA university. Method: In a first phase of work, participants answered open-ended questions about the behaviours they associated with IPV and related terms. In phase 2, participants categorised the behaviours identified in phase 1. In phase 3, consensus was reached by the 12 women who completed all three phases of work. Results: Women agreed on a list of 45 behaviours that constitute IPV as well as behaviours that fall into a 'grey area', with many of the latter occurring between boyfriends/girlfriends. Conclusion: Findings from the study contribute to the current knowledge base concerning IPV among US college students and their understanding of which behaviours are acceptable by intimate partners and which are not. Future research is needed with a larger more representative sample to extend the current findings. However, interim findings can be used to drive future research and may provide some insight into current student perceptions of IPV.